English From Message to Vibe: TikTok and Hybrid Political Communication in the 2024 UK Election - García Santamaría, Sara; Grantham, Susan; Grant, Kai (Estudios sobre el Mensaje Periodístico, 2026)
The 2024 UK general election has been widely described as the country’s first “TikTok election”, reflecting the platform’s growing role in political campaigning, particularly among younger audiences. This article examines how Labour and the Conservative Party adapted political communication to TikTok’s platform affordances through the use of popular culture, pop culture, and digital vernaculars. Empirically, the article draws on a content analysis of 175 videos posted by both parties between 30 May and 4 July 2024. Analytically, it conceptualises these practices through the lens of cultural vernacularisation and affective orientation, focusing on the hybridisation of symbolic (message-first) and pre-symbolic (vibe-first) communication. The findings show that while both campaigns relied on cultural mediation, Labour more consistently employed humour-driven, transgressive, vibe-oriented formats, whereas Conservative content more often combined cultural framing with explicit claims, warnings, and evaluative judgements. The article argues that TikTok campaigning does not signal the erosion of political meaning, but its reconfiguration through hybrid communicative architectures in which affective orientation and symbolic articulation operate together. More broadly, the study highlights how platform-native campaigning reshapes the conditions under which political communication reaches electorates who are increasingly disengaged from traditional political channels, such as young voters